ANALISIS PERMINTAAN PRODUK ROTI MENGGUNAKAN METODE TRIPLE EXPONENTIAL SMOOTHING - Supriyanti, Yanti; Nurselvi (Universitas Pamulang, 2025)
CV. Larissa Boga Utama is local businesses moving in the food industry, in recent years experienced an increase in product demand due to changes in its marketing system through social media and e-commerce. However, the inventory management process is still carried out manually without demand planning. This study aims to analyze demand planning using the Triple Exponential Smoothing (TES) method. The forecasting results using the TES method with two years of historical sales data show a demand of 1,990 units for 2025, with a MAPE accuracy of 3.08% (very good category) and an MSE of 56.05. The results show that the TES method is effective in improving the efficiency of demand and inventory management at CV. Larissa Boga Utama..